Prognostic role of clinical and biological factors and parameters of hormonal profile in patients with primary inoperable HER2-negative breast cancer - Natalia I. Samaneva (IP Habib O.N., 2021)
Relevance. Breast cancer (BC) is among the most common cancers and the leading causes of cancer death in women worldwide. Much attention is paid to the problem of its hormoneresistance; however, the issues of using prognostic markers and predictors in routine cancer clinical practice remain unresolved.